Infertility specific quality of life and gender role attitudes in German and Hungarian involuntary childless couples = Infertilitätsbezogene Lebensqualität und persönliches Geschlechtsrollen-verhalten infertiler Paare in Deutschland und in Ungarn - Cserepes, Réka Eszter; Bugán, A.; Korösi, T.; Toth, Bettina; Rösner, Sabine; Strowitzki, Thomas; Wischmann, Tewes (Geburtshilfe und Frauenheilkunde, 2014)
As gender role attitudes and the evaluation of parenthood and childlessness have subtle variations in each society, cross-country studies focusing on infertility are needed to draw a complex picture in the psychosocial context of infertility. This study investigates similarities and differences between German and Hungarian infertile couples regarding infertility specific quality of life and personal gender role attitudes. >Methods: A cross-sectional study was conducted with data of 540 participants (270 couples) attending the first fertility consultation in one fertility clinic in Germany and in five fertility clinics in Hungary. Data were collected between February 2012 and March 2013. Two psychological questionnaires were applied: The FertiQoL to measure infertility specific quality of life and the PAQ to measure gender role attitudes like “instrumental” acting (as a traditional “masculine” attitude) and “expressive” communicating (as a traditional “femine” attitude) and their combinations “combined” attitude (as both “instrumental” and “expressive”) and “neutral” attitude (neither “instrumental” nor “expressive”). German couples seeking assisted reproduction treatment are older aged and have longer lasting relationships than Hungarian couples. Hungarian couples scored higher on all quality of life scales than did German couples. In the Hungarian group, “combined” attitudes (use of both “expressive” and “instrumental” attitudes) is associated with higher levels of quality of life compared with other gender role attitudes. In the German group, individuals with “combined” attitudes seem to show better quality of life than those in “expressive” and “neutral” clusters. Conclusions: The strategy of using combined “expressive” and “instrumental” attitudes proved to act as a buffer against infertility-related stress for both members of the couple in two European countries and can therefore be recommended as helpful in counselling the infertile couple.
Gesehen am 23.10.2020